A statistical study about vaccines used against Covid-19 in Nineveh Governorat Iraq - Khalidah Nayyef Mustafa (Public Health of Indonesia)
Background:A total of 518 individuals vaccinated with three different COVID-19 vaccines were included in this study. The majority received the Pfizer vaccine, which was associated with mild side effects, while others experienced more severe symptoms such as headache and fever.